Preparation and clinical translation of (99m)Tc-PSMA-11 for SPECT imaging of prostate cancer - Vats, Kusum (Medchemcomm, 2019)
This study explores the feasibility of radiolabeling the HBED-CC-PSMA (PSMA-11) ligand with Tc-99m for SPECT imaging of prostate cancer patients. (68)Ga-HBED-CC-PSMA (PSMA-11) is used clinically for PET/CT imaging of prostate cancer (PCa) patients. However, a PET/CT facility may not be affordable and/or accessible to remotely located health centers. Thus, economic considerations require development of a SPECT-based tracer to provide low cost effective health care to the entire global population. Hence, radiochemical parameters were varied and optimized to obtain the maximum radiochemical yield of (99m)Tc-PSMA-11. (99m)Tc-PSMA-11 could be prepared in 60 ± 5% radiochemical yield and >98% radiochemical purity with a specific activity of 15 ± 5 GBq μmol(–1). The radiotracer exhibited high stability in vitro in human serum after 24 h. A cell uptake of 15.2 ± 1.2% was observed for (99m)Tc-PSMA-11 in PSMA-positive prostate carcinoma LNCaP cells. Rapid clearance from blood, liver, intestine, lungs and other major organs was observed during normal biodistribution studies. The radiotracer, (99m)Tc-PSMA-11, exhibited physiological distribution in salivary and lacrimal glands similar to that of (68)Ga-PSMA-11 in mice and successfully identified primary tumors as well as metastatic lesions in human patients. This study thus highlights successful radiolabeling of HBED-CC-PSMA with Tc-99m and the potential of (99m)Tc-PSMA-11 as a SPECT imaging agent for PCa.